Construction and application of workover priority evaluation model for surface coalbed methane low production wells based on Entropy-TOPSIS - Yanhe Li; Lin Zhu; Runsheng Lv; Runsheng Lv; Xiaoming Ni (Frontiers in Energy Research, 2024)
Affected by geology and mining, a certain number of low-yield wells will appear after a period of production in coalbed methane wells, and technical repairs are urgently needed to restore their production capacity to the maximum. Therefore, it is of great significance to establish a reasonable and feasible theoretical standard to evaluate the workover priority of CBM wells for the efficient utilization of CBM resources. From the perspectives of technical feasibility and economic rationality, eight key indicators that affect the cost performance of CBM well workover are screened. Combining the entropy value method and the TOPSIS comprehensive ranking method, the surface coalbed methane well repair priority entropy value-TOPSIS comprehensive evaluation model was constructed, and the surface coalbed methane well repair priority evaluation was carried out by taking 9 surface coalbed methane wells that urgently needed to be repaired in a mine as the evaluation objects. The evaluation results show that among the economic indicators, the average gas production per meter in the 30 days before the coal bed methane well was stopped and the cumulative gas production per meter before the stop had a relatively high weight, which were 29.68% and 13.83% respectively, This shows that in coalbed methane well workover operations, the long-term gas production potential of the coalbed methane well and the gas production capacity when disturbed by harmful factors are the decisive factors affecting the priority of coalbed methane well workover; Among the technical indicators, the degree of casing deformation and the depth of the coalbed methane well have a relatively high weight, accounting for 11.34% and 9.90% respectively, This shows that the smaller the deformation of the wellbore casing and the shallower the depth of the coalbed methane well, the higher the priority of the workover of the coalbed methane well; The ranking of the production recovery rates of the three coalbed methane wells in the Pingdingshan mining area after workover operations is consistent with the results output by the evaluation model, which proves that the evaluation model is reasonable for determining the priority of workovers for damaged wellbores; This evaluation model can provide a theoretical reference for small and medium-sized coalbed methane development companies to determine the priority of workovers.